Le chêne, le cheval, le bûcheron. Une collection d’écorçoirs des XIXe et XXe siècles au musée des civilisations de l’Europe et de la Méditerranée - Narjys El Alaoui (Revue d'ethnoécologie)
The Musée National des Arts et Traditions Populaires currently Musée des Civilisations de l’Europe et de la Méditerranée-MuCEM since 2005 welcomed from its inception a collection of uncommon items transferred from the Musée d'Ethnographie du Trocadero (MET) he enhanced until 1971. These are barkers from different periods and types (stone, bone, bone and metal, wood and metal), used to remove the bark of oak for tanneries before disappearing in the late 1870s.Nearly a century separates the input of the first barker (1888) from the last (1971). Although the documents concerning their manufacture and use are scarce, brief, scattered and unknown, they have the credit of being sometimes contemporary to the tools, even if we may regret the lack of illustration of the tool in its historical context. For all these reasons they are appreciated, this is why we felt appropriate to gather them in this paper.